Hubungan Antara Pengetahuan dan Sikap dengan Konsumsi Sugar Sweetened Beverages (SSBs) pada Mahasiswa Kesehatan dan Non Kesehatan Universitas Airlangga - Lina Ali Baraja; Trias Mahmudiono (STIKES Columbia Asia Medan, 2025)
Sugar Sweetened Beverages are beverages that contain added simple sugar, provide energy but have minimal nutrition. College students often consume these sweet drinks. Knowledge and attitude play an important role in the tendency to consume SSB. This study aims to analyzed the relationship between knowledge and attitude with SSB consumption among health and non-health students of Airlangga University. The research method used a quantitative approach with an observational cross-sectional design. The population includes 426 undergraduate students of Islamic Economics Study Program and Faculty of Public Health semester 4, with a sample of 90 students. Data were collected through a questionnaire that measures knowledge, attitude, and SSB consumption using the Semi-Quantitative Food Frequency Questionnaire (SQFFQ). Bivariate analysis was performed using the Chi Square test. The results showed that most respondents were 19-20 years old, mostly female, and had normal nutritional status. There was a significant difference in knowledge (p < 0.001 ) and attitude (p = 0.032) between health and non-health students. However, no relationship was found between knowledge and attitude with SSB consumption in both groups of student.